KONSEPTUAL DESING PENINGKATAN KAPASITAS TUPOKSI PEGAWAI SEBAGI TUGAS TAMBAHAN DI LINGKUNGAN POLTEKKES KEMENKES MALANG - Trisnanto, Puguh Yudho; Kholidah, Diniyah; Prabowo, Yudhi; Fadila, Rizky; Pitoyo, Zani; Lala, Handy (DINAMIKA DOTCOM, 2019)
Conceptual Desing of Increasing the Capacity of Employee Autonomy as Tamabahan's Duty in Malang's Ministry of Health Poltekkes Environment. Information data maps are study analyzes related to DS, DT, Process and Store (data storage information used). With this information, information is produced with respect to [1]. DADL levels 0.1 and 0.2 which describe the function of the process as i1 = lab management items, i2 = number of lab visits, DADF describes the process function to calculate the total number of lab visits Psd = 1, Pst = 1 so that it produces DS = 1 and DT = 1, [2]. DADL level 2.0 which describes the function of the process as i1 = lab management item, i2 = number of practicum schedules, DADF explains the process function calculates the total number of practicum activity schedules Psd = 1, Pst = 1 so as to produce DS = 1 and DT = 1 [3]. DADL level 3.0 which describes the function of the process as i1 = lab name item, i2 = number of practicum schedule, DADF explains the function of the calculation process using practicum lab Psd = 1, Pst = 1 so as to produce DS = 1 and DT = 1 1 [4]. Level 4.0 DADL which describes additional task functions as i1 = Kode_SOP, i2 = sum of debugging, DADF explains the process function of the number of additional tasks Psd = 1, Pst = 1 so that it produces DS = 1 and DT = 1 [5]. Level 4.0 DADL which describes additional task functions as i1 = Kode_SOP, i2 = sum of debugging, DADF explains the process function of the number of additional tasks Psd = 1, Pst = 1 so that it produces DS = 1 and DT = 1 [6]. DADL level 5.0 which describes the tupoksi function as i1 = Kode_tupoksi, i2 = nomor_tupoksipgw, DADF explains the function of the number of functions of Psd = 1, Pst = 1 so that it produces DS = 1 and DT = 1 Keywords: Source data, Destination Data, Process, Store, conceptual design